2009
DOI: 10.1371/journal.pone.0005689
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inhibition of NF-κB Activation Protects from Silicosis

Abstract: BackgroundSilicosis is a complex lung disease for which no successful treatment is available and therefore lung transplantation is a potential alternative. Tumor necrosis factor alpha (TNFα) plays a central role in the pathogenesis of silicosis. TNFα signaling is mediated by the transcription factor, Nuclear Factor (NF)-κB, which regulates genes controlling several physiological processes including the innate immune responses, cell death, and inflammation. Therefore, inhibition of NF-κB activation represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 49 publications
3
38
2
2
Order By: Relevance
“…However, TNF makes an important contribution toward the survival of macrophages to silica. Previously, we found that inhibition of TNF-mediated NF-kB activation significantly enhanced silica-induced apoptosis in RAW 264.7 macrophages and worsened silica-induced lung injury in mice (1,27). The current work demonstrates that macrophages differ in their secretion of TNF in response to silica and that TNF expression in RAW 264.7 macrophages triggers TNFR1-signaling events that diminish ROS production.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, TNF makes an important contribution toward the survival of macrophages to silica. Previously, we found that inhibition of TNF-mediated NF-kB activation significantly enhanced silica-induced apoptosis in RAW 264.7 macrophages and worsened silica-induced lung injury in mice (1,27). The current work demonstrates that macrophages differ in their secretion of TNF in response to silica and that TNF expression in RAW 264.7 macrophages triggers TNFR1-signaling events that diminish ROS production.…”
Section: Discussionsupporting
confidence: 55%
“…Exposure to silica is common; .2 million people are exposed to silica in the United States every year, and silicosis remains a global threat for which no specific therapy is available (1).…”
mentioning
confidence: 99%
“…A similar connection has been described in a mouse model of experimental autoimmune thyroiditis where a reduction in TNF activity was associated with decreased fibrosis [43]. In separate studies, systemic inhibition of NFκB with BAY 11 in mouse models of silica-induced lung injury or liver injury induced by carbon tetrachloride resulted in reduced fibrosis [44, 45]. In addition, a link between TNF and TGF-β expression has been demonstrated in TIMP3 KO mice.…”
Section: Discussionmentioning
confidence: 58%
“…This implied that blockade of the NFkB pathway might protect against lung fibrosis by decreasing YY1 expression. Interestingly, a recent report demonstrated that Bay11-7085 decreased silica-induced inflammation and collagen deposition (34), although potential effects of NF-kB inhibition on YY1 expression were not investigated in that report. Thus, in addition to promoting the expression of cytokines, chemokines, and other inflammatory mediators, these data suggest that by inducing YY1 expression, NF-kB promotes the expression of genes involved in tissue repair responses.…”
Section: Discussionmentioning
confidence: 93%